2020
DOI: 10.35484/pssr.2020(4-iii)48
|View full text |Cite
|
Sign up to set email alerts
|

Support Needs of Novice Public-School Teachers for Effective Management of Elementary Level Classrooms in Lahore

Abstract: The purpose of this study was to develop an understanding of the support needs which novice teachers considered essential in their initial three years of service. A basic qualitative research design was used, and semi-structured interviews were conducted with a purposive sample comprising of 20 novice teachers who had less than three years of teaching experience at public-elementary schools in Lahore. The result of the study indicated that novice teachers considered that both principal and senior teachers shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…4-5). Poorly managed classrooms lead to ineffective teaching and learning (Saleem, Muhammad, & Masood, 2019, 2020a, 2020b. Effective classroom management is usually dependent on the standard of establishing a conducive environment of the classroom encompassing effective student-teacher relations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…4-5). Poorly managed classrooms lead to ineffective teaching and learning (Saleem, Muhammad, & Masood, 2019, 2020a, 2020b. Effective classroom management is usually dependent on the standard of establishing a conducive environment of the classroom encompassing effective student-teacher relations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The support from the principal is the vital need of novice teachers. However, it is observed that mostly this support is not available to novice teachers in Pakistan (Saleem et al, 2020). Novice teachers are generally given low achieving and overcrowded classes at the start of their careers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Otherwise, retaining novice teachers in the school may become a challenge for the principal (Kalogrides et al, 2013). Novice teachers experience a lack of support from the administration, particularly the principal, providing material support (Saleem et al, 2020). They elaborated that the absence of support in terms of the instructional material affects their overall classroom management.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations